Change of Tensile Properties with Aging Time and Temperature in Al-Si-Cu-Mg 354 Cast Alloys with/without Minor Addition of Ni and/or Zr - J. Hernandez-Sandoval; M. H. Abdelaziz; E. A. Elsharkawi; A. M. Samuel; F. H. Samuel (Advances in Materials Science and Engineering)
The principal aim of the present research work was to investigate the effects of minor additions of nickel and zirconium on the strength of cast aluminum alloy 354 at room temperature (25°C). A decrease in tensile properties of ∼10% with the addition of 0.4 wt.% nickel is attributed to a nickel-copper reaction which interferes with the formation of Al2Cu precipitates. The platelet-like phases (Al,Si)3(Zr,Ni,Fe) and (Al,Si)3(Zr,Ti) are the main features observed in the microstructures of the tensile samples of alloys with Zr additions. The reduction in mechanical properties is due to the increase in the percentage of intermetallic phases formed during solidification; such particles would act as stress concentrators, decreasing the alloy ductility. The main effect of Zr addition lies in a significant reduction in the alloy grain size ∼40%, rather than an increase in the mechanical properties. Quality index charts could be used in assessing the effects of the Ni and Zr additions to the base alloy, as well as evaluating the heat treatment relationships to the alloy tensile properties, in particular when the system shows multiple precipitation reactions. Due to the high liquidus temperature of the Al-Zr binary phase diagram, addition of Zr beyond 0.2% is not recommended to avoid undissolved Zr.